(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
This article discusses such concepts as natural monopolies, the functions of natural monopolies, one of the main problems of the lack of fair competition among enterprises, the main types of monopoly, the characteristic features of a natural monopoly. The main provisions of the Federal Law "On Natural Monopolies" are analyzed, in particular: the possibilities for regulatory bodies to influence the activities of natural monopoly companies, methods of regulation of natural monopolies, the rights of regulatory bodies, the environment for the functioning of regulatory bodies.